2021
DOI: 10.21512/bbr.v12i1.6454
|View full text |Cite
|
Sign up to set email alerts
|

How to Expand Repurchase Intention? The Intervening Impact of Attitude towards Mobile Shopping

Abstract: The research aimed to investigate and test the attitude toward mobile shopping as a mediating variable at the relationship between perceived usefulness and perceived risk against repurchase intention. The research used a quantitative approach to explain the relationship between research variables. The used sampling technique was purposive sampling, with a total sample of 200 mobile shopping users in Central Java. Data collection was carried out using a questionnaire. The obtained data were processed using the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…This is due to the different characteristics of the respondents, where in Hieronanda & Nugraha's research (2021) the characteristics of the respondents are from 19-48 years old and the respondents in the study are still very broad because they target the Indonesian community. Furthermore, the research by Nurcholis & Ferdianto (2021) showed that the characteristics used in this study were 17-35 years old and in the Central Java region. With this, in contrast to the characteristics of the respondents used in this study, the age characteristics of the respondents are 13-44 years, East Java region, and purchases on e-commerce platform sites that focus on the TikTok Shop application.…”
Section: Perceived Risk Affects Repurchase Intentionmentioning
confidence: 89%
“…This is due to the different characteristics of the respondents, where in Hieronanda & Nugraha's research (2021) the characteristics of the respondents are from 19-48 years old and the respondents in the study are still very broad because they target the Indonesian community. Furthermore, the research by Nurcholis & Ferdianto (2021) showed that the characteristics used in this study were 17-35 years old and in the Central Java region. With this, in contrast to the characteristics of the respondents used in this study, the age characteristics of the respondents are 13-44 years, East Java region, and purchases on e-commerce platform sites that focus on the TikTok Shop application.…”
Section: Perceived Risk Affects Repurchase Intentionmentioning
confidence: 89%